2015
DOI: 10.1007/s00011-015-0840-y
|View full text |Cite
|
Sign up to set email alerts
|

Alterations in Hoffa’s fat pad induced by an inflammatory response following idealized anterior cruciate ligament surgery

Abstract: Sustained long-term pathological changes stemming from inflammation are present in IPFP tissue after ACL-R surgery and may compromise the long-term integrity of the knee joint.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(23 citation statements)
references
References 47 publications
0
23
0
Order By: Relevance
“…A significant correlation between ACL tear and alteration in IFP appearance, most commonly focal edema, has been reported based on MRI observations 1 . Histological analysis in sheep following ACL reconstruction revealed increased cellularity, vascularity and innervation present in the IFP at 2 and 20 weeks post-surgery 25 The MRI sequence and cadaveric video demonstrate the deformation of the IFP and narrowing of the anterior interval during flexion from 37º to 8º. In extension it is clear that the IFP is compressed by the anterior femur and tibia, the anterior horns of the menisci, and the intermeniscal ligament.…”
Section: Discussionmentioning
confidence: 88%
“…A significant correlation between ACL tear and alteration in IFP appearance, most commonly focal edema, has been reported based on MRI observations 1 . Histological analysis in sheep following ACL reconstruction revealed increased cellularity, vascularity and innervation present in the IFP at 2 and 20 weeks post-surgery 25 The MRI sequence and cadaveric video demonstrate the deformation of the IFP and narrowing of the anterior interval during flexion from 37º to 8º. In extension it is clear that the IFP is compressed by the anterior femur and tibia, the anterior horns of the menisci, and the intermeniscal ligament.…”
Section: Discussionmentioning
confidence: 88%
“…The fibrosis of the IPFP may cause of AKP, causing higher pressure in the knee joint, and, in turn, decreasing functioning. Moreover, previous animal model studies have demonstrated both histopathological and immunohistochemical changes, including fibrosis, vascularity, and proliferation of small vessels accompanying free nerve endings in the IPFP, after ACLR, trauma, or a patellar tendinopathy model [25][26][27] . Increased free nerve endings may reduce the threshold of pain sensation.…”
Section: Discussionmentioning
confidence: 99%
“…Some recently published studies also emphasize the altered biologic responses in the fat pad after ACL reconstruction that can also be associated with poor outcome. In the study of Solbak et al, inflammational and fibrotic changes are found in the fat pad after ACL reconstruction on a sheep model [ 39 ]. Wang et al also found fibrotic changes which are correlated with magnetic resonance imaging after ACL transaction on a rat model [ 40 ].…”
Section: Discussionmentioning
confidence: 99%